A bill to compensate the owners of slaves who may be executed (House doc. (North Carolina. General Assembly. House of Commons), 1852)
1852 North Carolina House bill which would compensate an owner of a slave who was executed for a capital offense. As part of a jury's duty after a guilty verdict, it was to also assess the value of the slave; the owner would receive two-thirds of that amount following execution.